Pembelajaran Asmaul Husna Sebagai Bentuk Pengamalan Tauhid (Studi Living Qur’an di SD Islam Nazhirah Bandar Lampung) - Sherfina Indah Aprilia; Muh. Wasith Achadi (Departement of Mathematics Education, 2023)
The background of this research problem is to see the existence of the Tawhid practice process that has not been applied optimally, especially for students in the field of education. The process of practicing monotheism itself is considered to be limited to learning a science without applying and practicing it in everyday life. So that with these problems, the researchers conducted research to find answers to the formulation of the problem as follows: 1) How is the implementation of the process of using Asmaul Husna; 2) What are the results obtained from the use of Asmaul Husna; and 3) What are the obstacles faced from the process of using Asmaul Husna. This type of research is a qualitative research based on field research analysis with an ethnographic approach. Data collection techniques were carried out through observation, interviews, and documentation. While the research data were analyzed using qualitative analysis, namely data reduction, data presentation, verification, and conclusions. The data validity test in this study is data triangulation, namely technical triangulation, source triangulation, and time triangulation. The results of this study indicate that: First, the implementation of Asmaul Husna learning as a form of practicing monotheism in Nazhirah Islamic Elementary School Bandarlampung is carried out through subject-based main activities and supporting activities which include all additional activities outside the learning process. Second, the results obtained by students in using Asmaul Husna as a form of practicing monotheism can be seen through three aspects of student development which include cognitive, affective, and psychomotor. Third, the obstacles faced are felt when the online learning process shows less than optimal results.